Penambahan Vitamin E dan Ekstrak Daun Sirih Cina terhadap Kelangsungan Hidup dan Perkembangan Gonad Ikan Selincah - Heru, Heru; Tanbiyaskur, Tanbiyaskur; An-Nisa, Shofia; Amelia, Anissa (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Heru H., Tanbiyaskur T., An-Nisa, S., Amelia, A., Adinda, O., Khairunnisa, R., Prihartina, S., & Septiana, T. (2023). Addition of vitamin e and peperomia pellucida leaves extract on survival and development of fish gonad. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 490-497). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Belontia hasselti, a valuable economic fish, has faced limited domestication prospects. To address this, an experiment was conducted to assess the impact of supplementing their diet with vitamin E and Peperomia pellucida leaf extract on gonad development. Vitamin E, an essential micronutrient, influences fish reproductive performance, while Peperomia pellucida contains antibacterial and antioxidant compounds that inhibit bacterial growth. This experiment aimed to assess how adding Peperomia pellucida leaf extract and vitamin E to commercial fish feed would affect the gonad development of Belontia hasselti, with the goal of domestication. The study involved two treatments: P1 (standard feed without enrichment) and P2 (enriched with vitamin E and Peperomia pellucida extract). Results revealed significant improvements in gonad maturation, with males reaching TKG III and females TKG IV. Male GSI stood at 0.57%, females at 2.02%, and fecundity at 3,593 eggs. Fish showed absolute weight and length growth of 6.15 grams and 1.7 centimeters, with a survival rate of 83.3%. In conclusion, supplementing commercial fish feed with vitamin E and Peperomia pellucida extract positively impacted Belontia hasselti gonad development, improving maturation levels and reproductive outcomes. To ensure consistent results, it is advisable to tailor the use of these additives in commercial feed to meet the specific needs of the fish.